FAKTOR PENYEBAB IBU TIDAK MEMBERIKAN ASI EKSKLUSIF - Fatimah, Siti; Wardani, Endah Kusuma; Herniyatun, Herniyatun; Sumarlan, Sumarlan (Ensiklopedia of Journal, 2025)
Abstract: Exclusive breastfeeding is the main feeding for infants by only providing breast milk without additional food or drinks, including water. Based on data obtained from Puskesmas Bangetayu Semarang, in March 2023 the coverage rate of exclusive breastfeeding was 61%, and in April 2024 the coverage rate of breastfeeding was 59%, and the coverage rate of breastfeeding.  Preliminary studies conducted at Puskesmas Bangetayu Semarang found that 7 out of 10 mothers were less than optimal in breastfeeding. Some respondents had good breast milk production, but due to lack of knowledge about proper breastfeeding, they gave additional food other than breast milk. The research design used in this study was cross sectional. The research was conducted in the Bangetayu Health Center work area in July 2024. The population is mothers who have babies aged 0-6 months in the Bangetayu Semarang Health Center area, especially in Bangetayu Wetan Village, consisting of 130 people. The sample amounted to 109 respondents. The sampling technique used in this study was Consecutive Sampling. Data analysis was done univariate and bivariate. The results showed a relationship between family support (p value: 0.046) and maternal knowledge (p value: 0.038) on exclusive breastfeeding.Keywords: Exclusive breastfeeding, family support, maternal knowledge.